The Influence of Transformational Leadership on Intergenerational Employee Resilience Through Technological Innovation in Industry 5.0 - Antonius Budi Wibowo; Wilson Bangun; Lina Anatan (proceedings.icesy, 2026)
The rapid development of digital technology and generational diversity in the workforce has increased the need for resilient employees in the era of Industry 5.0. This study aims to examine the effect of transformational leadership on employee resilience across generations through technological innovation as a mediating variable. A quantitative explanatory approach was employed using survey data collected from 100 employees of Media Cooperation selected through convenience sampling from a population of 256 employees. Data were analysed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that transformational leadership has a positive and significant effect on technological innovation and employee resilience. Technological innovation also significantly influences employee resilience and mediates the relationship between transformational leadership and employee resilience. These findings suggest that transformational leaders who promote innovation and support digital adaptation are more capable of strengthening employees’ adaptive capacity in a multigenerational workforce. The study highlights the importance of human-centered leadership and innovation in fostering organizational resilience. In conclusion, transformational leadership, supported by technological innovation, is a key driver of employee resilience in Industry 5.0-oriented organizations.